2008
DOI: 10.1017/s1461145707008152
|View full text |Cite
|
Sign up to set email alerts
|

β2 Nicotinic acetylcholine receptor availability in post-traumatic stress disorder

Abstract: Availability of nicotinic acetylcholine receptors containing beta2 subunits (beta2-nAChRs) was studied in unmedicated, symptomatic patients with post-traumatic stress disorder (PTSD) and healthy control subjects, all current non-smokers. A subgroup of participants had a history of smoking. Availability of beta2-nAChRs in the mesiotemporal cortex, prefrontal cortex, thalamus and striatum was determined using the radiotracer [123I]5-IA-85380 ([123I]5-IA) and single-photon emission computed tomography (SPECT). PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…In addition, infusions of the high-affinity nAChR antagonist DhβE into the dorsal hippocampus precipitated withdrawal deficits in both contextual (Davis & Gould, 2009) and trace fear learning (Raybuck & Gould, 2009). Overall, in line with the human studies linking hippocampal β2 nAChRs with PTSD (Czermak et al, 2008), results from the studies using acute, chronic, and withdrawal from chronic nicotine suggest that the effects of nicotine on hippocampus-dependent fear memories require the activation and upregulation of the high-affinity β2-containing nAChRs.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disorderssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, infusions of the high-affinity nAChR antagonist DhβE into the dorsal hippocampus precipitated withdrawal deficits in both contextual (Davis & Gould, 2009) and trace fear learning (Raybuck & Gould, 2009). Overall, in line with the human studies linking hippocampal β2 nAChRs with PTSD (Czermak et al, 2008), results from the studies using acute, chronic, and withdrawal from chronic nicotine suggest that the effects of nicotine on hippocampus-dependent fear memories require the activation and upregulation of the high-affinity β2-containing nAChRs.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disorderssupporting
confidence: 64%
“…Investigating the direct relationship between nAChRs and PTSD by using the radiotracer [ 123 I]5-IA-85380 ([ 123 I]5-IA) and single-photon emission computed tomography, Czermak et al (2008) found that PTSD patients who never smoked showed significantly higher β2 nAChR density in the mesiotemporal cortex including the amygdala and hippocampus compared to healthy individuals who never smoked. Furthermore, the same study found a significant correlation between β2 nAChR binding in the thalamus and the reexperiencing symptom among the PTSD patients.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…Importantly, using the radiotracer [ 123 I]5-IA-85380 and single-photon emission computed tomography (SPECT), Czermak et al (2008) demonstrated that non-smoker PTSD patients showed a significantly higher density of β2 nAChRs in the mesiotemporal cortex, including the amygdala and hippocampus, compared to non-smoker healthy individuals. These brain regions are widely related to pathogenesis of PTSD (Martin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes in nAChRs availability have been observed in patients suffering from post-traumatic stress disorders or depression. [19][20][21] Chronic social defeat stress (SD) parses the enduring behavioral abnormalities induced by stress and is believed to capture features of depressive-like states. 22 SD triggers an increase in DA VTA neuronal activity 23 that drives social avoidance.…”
Section: Introductionmentioning
confidence: 99%